Negative life events and maternal mental illness: A study of elite pregnant women in Accra metropolis - Vincent Valentine Akorli; Samuel Adjorlolo; Gideon Puplampu (International Journal of Africa Nursing Sciences, 2023)
The vulnerability of maternal mental illness (MMI) such as anxiety and depression among childbearing women is heightened during the periods of pregnancy mainly because of negative life events (NLEs). However, a major caveat in the literature relates to the overwhelming focus on women from disadvantaged socioeconomic background. Little is known about NLEs and MMI among women with relatively better socioeconomic background and high educational status, termed in this study as elite pregnant women. The study investigates the prevalence of NLEs and MMI (i.e., depression and anxiety) as well as the relationship between NLEs and MMI among elite pregnant women. A cross sectional survey design was used to collect data from 210 respondents recruited from three purposively selected health facilities in Greater Accra metropolis, namely Nyaho Medical Centre, Pentecost Hospital and Abokobi Health Centre. Self-report measures of NLEs, depression and anxiety were administered to the respondent. Data were analyzed using both descriptive statistics and inferential statistics, namely Pearson correlation and hierarchical linear regression. The study revealed that majority (n = 136, 64.8 %) of the respondents experienced at least particular NLEs and rated these events as stressful. The prevalence of symptoms of anxiety and depression were 42.4 % and 51.0 %, respectively. NLEs significantly and positively correlated with symptoms of anxiety but not with depression. Elite pregnant women are at risk of NLEs which can significantly influence their mental health. It is recommended that midwives and other health professionals pay attention to the NLEs of elite pregnant women for necessary support and intervention.